Match the New Product Development Project with its Context: Case Study of Composite Manifold in Wavin NV, Netherlands - Prasetio, Eko Agus (Jurnal Manajemen Teknologi, 2012)
This paper provides the frameworks and tools for matching the innovation and new product development project with its context in Wavin N.V., a European plastics converting company which develops, manufactures and markets total pipe systems. Where Wavin moves into new segment, Wavin applies its conventional internally-oriented approach to its innovation and new product development and as a consequence, it faces problems in terms of delay of time to market and increasing costs. The development of composite manifold is taken as an illustrative case of the problem that Wavin is facing. As indicated by the case, Wavin is trapped in a â€œone-size-fits-allâ€ approach in its innovation and new product development process. The paper is developed through the use of primary research in the form of in-depth interview and case-study discussions with innovation managers, program managers and marketing managers in Wavinâ€™s headquarters (Netherlands) and other European countries, and secondary research in the form of company data analysis and extensive literature review. Frameworks of newness and risk map as well as the corresponding scoring systems is elaborated and developed to increase the efficiency and effectiveness in Wavinâ€™s NPD.